Analisis Pengembangan Usaha Peternakan Sapi di Kecamatan Landono Kabupaten Konawe Selatan (Studi Kasus pada Anggota Kelompok Tani Budi Karya) - Novianty Demas; Ine Fausayana; Yusran Yusran (Department of Agribusiness, Halu Oleo University Jointly with Perhimpunan Ekonomi Pertanian Indonesia - Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2023)
Landono District has a potential area for developing a cattle breeding business, but cattle farming requires a considerable investment. The Budi Karya Farmers Group is one of the groups that conduct cattle farming in Landono District, South Konawe Regency. The research objective was to determine the feasibility of developing a cattle breeding business for members of the Budi Karya farmer group in Landono District, South Konawe Regency. Determination of the research location was carried out purposively with the consideration that in Landono District, there is a cattle business carried out by farmer groups. The number of respondents, namely all members of the Budi Karya farmer group, as many as 19 people and one of the officers from the livestock service who helped develop the cattle farming business in Landono District. Data analysis used feasibility and sensitivity analysis. The results of research on the development of a cattle farming business for members of the Budi Karya farmer group obtained an NPV value of Rp663.881.185, an NBCR value of 2,412, an IRR value of 35,97%, a PP value of 2 years four months, a production BEP of 2 heads and a BEP price of Rp389.153. The results of the sensitivity analysis of the cattle farming business of members of the Budi Karya farmer group to a 10% decrease in production and an increase in production costs of 10% meet the five eligibility assessment criteria so that the development of cattle farming business members of the Budi Karya farmer group is feasible to be cultivated or run.